2020
DOI: 10.1177/0003489420932593
|View full text |Cite
|
Sign up to set email alerts
|

Do Medical Students Receive Adequate Otolaryngology Training? A Canadian Perspective

Abstract: Objectives: Otolaryngology—head and neck surgery (OHNS) training has been found to be underrepresented in medical school curricula. The study aimed to assess (i) students’ clinical OHNS exposure, (ii) their confidence managing OHNS conditions, and (iii) the correlation between OHNS exposure and confidence managing OHNS conditions. Methods: Fourth-year medical students at two Canadian Universities completed a survey assessing baseline characteristics, OHNS training, and confidence managing OHNS conditions. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the Canadian curriculum, most instructional OHNS content outside of elective time did not contain opportunities for formal evaluation [16]. On the other hand, we found that the majority of our responders did provide an opportunity for evaluation, most commonly in a postelective meeting (74%), and most responders evaluate students through a formal evaluation from (70%).…”
Section: Evaluation Of Elective Studentsmentioning
confidence: 84%
“…In the Canadian curriculum, most instructional OHNS content outside of elective time did not contain opportunities for formal evaluation [16]. On the other hand, we found that the majority of our responders did provide an opportunity for evaluation, most commonly in a postelective meeting (74%), and most responders evaluate students through a formal evaluation from (70%).…”
Section: Evaluation Of Elective Studentsmentioning
confidence: 84%
“…Even before the COVID-19 pandemic, studies had shown that medical graduates do not feel prepared for several different skills that one would expect from a medical graduate [ 33 , 34 ]. In a recent study, Canadian medical school graduates stated that a majority of students had minimal exposure to ENT during medical school and most of them have low confidence managing ENT conditions [ 35 ]. Review courses and obligatory curricular tests of skills such as United States Medical Licensing Examination (USMLE) Step 2 Clinical Skills that obliges medical students to review and train a broad spectrum of clinical skills could certainly help to reduce these individual deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…The Pakistan Medical and Dental Council is equipped with important role in determining the need of the community and inhibiting to accept the world-wide inclination which can have counterproductive effect in our set up as majority of individuals have access to GP. If the general practitioner is not specialist in this particular field than due to deficiencies, a proper care and referral cannot be made 20 . Furthermore, otolaryngology specialists and consultants are also in constant demand for specialized otolaryngology problems within the country.…”
Section: Discussionmentioning
confidence: 99%